Estudio de pre factibilidad para la Produccion de Piñon Blanco (Jatropha Curcas) EN 410.73 Has. En El Fundo San Alberto - Chepen - La Libertad - Mariños Flores, Emily Giovanni (2016)
The cultivation of Jatropha curcas L., is potentially economically and ecologically viable alternative, given its high yields for the production of vegetable oil fuel and its production does not compete directly with food crops. You also have medicinal properties. This culture was framed in the contexto of the Mechanism of Clean Development projects - CDM (Kyoto Protocol) and CO2 capture trunk and roots. The pre-feasibility study for the production of White Pine Nut (Jatropha Curcas) in 410.73 hectares in the Fundo San Albero - Chepén is to measure the economic, financial profitability and sustainability of this activity as well as the positive environmental impact. This project is carried out specifically tech drip irrigation which has a high profitability, even considering high investment costs. To achieve a good quality product a study in the province of Chepén about their growing conditions and characteristics of the soils, presence of labor demanded by the project, the areas and species grown in the area, etc. develops. Besides an economic study of the project, where resources necessary for its development and management, price and volume analysis Pinion White marketed in the national and international market are presented, and based on these results, presented price projections made and volumes that will be used to determine the revenue generated by the project, the profitability indicators IRR and NPV are presented as a sensitivity analysis.